Penerapan Metode K-Means Dalam Mengelompokkan Banyaknya Desa/Kelurahan Menurut Jenis Pencemaran Lingkungan Hidup Berdasarkan Provinsi - Agus Tiranda Sipayung; S Saifullah; Riki Winanjaya (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
Environmental pollution is hazardous for every living thing; environmental pollution can cause an imbalance in the environment or existing ecosystem. This study discusses the grouping of villages according to the type of environmental pollution based on the provinces in Indonesia. The method used is DataMining with the K-means Clustering algorithm. By using this method, the data obtained can be grouped into 2 clusters. This study uses secondary data, namely data obtained through intermediary media recorded on the Central Bureau of Statistics website with the URL address: http://www.bps.go.id. The results obtained in this study are grouping environmental pollution into 2 clusters, namely the highest cluster and the lowest cluster. In this research, it is hoped that it can provide input to related government parties to pay more attention to the provinces included in the highest cluster to tackle environmental pollution in the province.